REPRESENTAÇÕES SOCIAIS DA FAMÍLIA SOBRE O DESENVOLVIMENTO MORAL DE CRIANÇAS E ADOLESCENTES NA PERSPECTIVA DA EDUCAÇÃO - Oliveira, Vânia de (2016)
This study focuses on Social representations (SR) of children's and adolescent's moral development in the context of the relationships between the institutions family, school and social projects developed after/before school hours. The research main question is: What are the family social representations of the role of education, at home, at school and in the after/before school hour social projects, regarding their children moral development? The main aim of this study was to learn through analytical reflection, the characteristics of family social representations of the children’s and adolescents’ moral development in the education perspective. The study was carried out in an institution called ‘Guarda Mirim’ which develops social projects with children who are in a situation of social vulnerability in the city of Ponta Grossa, state of Paraná. The research was developed as a quanti-qualitive study through interviews with 60 families of students whose age varied from six to sixteen. The theoretical and methodological background was based on the dimensional (MOSCOVICI, 1978, 2012) and dynamic (JODELET, 2001, 2007, 2009) approaches to Social Representations; Piaget’s (1994,1996) Moral and Psychological development and Genetic Epistemology. Content analysis was employed to discuss the data, aided by the programs ALCESTE and SPSS. The analysis of this educational context revealed three SR: “usefulness of school”, regarding job market/future;“education originates at home”, making the ‘Guarda Mirim” an extension of their homes; and “educating at home means correcting”. Moral values are associated to the heteronomous morality, and parents think that the Guarda Mirim caters for that in a better way than the school.Therefore, the research presents some pedagogical contribution as follows: the importance of teacher education to better understand the methodological approaches that lead to children’s and adolescents’ moral development; the necessity and hardship experienced by the families in social vulnerability demand full time schools to help and contribute to educate students coming from these families; the right children and adolescents have to quality education, aiming at citizenship and social participation, requires moral and ethical development.